Cuidado e autocuidado em situação de vulnerabilidade: designantropologia para a cocriação de futuros possíveis com mães de crianças com espectro autista. - MAIA, Alessandra Maria Silva Santos (2024)
The present study addresses the theme of "Care and Self-Care in Vulnerable Situations" through designantropology to the co-creation of possible futures in collaboration with mothers of children diagnosed with Autism Spectrum Disorder (ASD). Based on a qualitative approach, encompassing an in-depth exploration of exchanges between co-researchers, from a perspective that transcends mere assistance, understanding care as a multidimensional phenomenon. The research adopts an interdisciplinary approach, combining elements of designanthropology and feminism, with the aim of contextualizing mothers' experiences within a broader context of power and gender relations. The main focus lies on understanding the complex interconnection between the care provided by mothers to children with ASD and their own self-care process, an aspect often neglected in vulnerable contexts. The research also includes an analysis of the gaps in public policies designed to support families on this journey, as well as the way these mothers face and shape their daily realities. The methodology involves participatory action research, allowing mothers to actively participate in the co-creation of strategies and solutions that aim to improve the quality of life of their families. The study sought to take a close look at the role of these mothers, highlighting their experiences, challenges and aspirations, providing valuable insights for more effective and comprehensive approaches to supporting families in similar situations. The general and specific objectives of the study were outlined, mapping theories, discourses and practices related to care, identifying the vulnerabilities perceived by mothers, co-creating from designanthropology approaches for reflection and stimulation of possible futures, and reflecting on the process of co creation and its contribution to promoting self-care and imagining futures. The research was based on correspondence practices between researchers and participants, applying concepts of designanthropology to reflect on mothers' experiences and promote social changes resulting in co-creation and projection of futures and possibilities. As a result of the research, it was found that co-participating mothers need to be included in the planning of macropolitcs that provide them with minimum conditions so that they can exercise care and self-care. And the reflections that were made can serve as a starting point for future correspondence between designers and co-participants.